John Lennon - Memos of a Life (KULT_online, 2013)
The publication of The John Lennon Letters by the journalist and Beatles-biographer Hunter Davies is part of an ongoing Beatles renaissance. The book, published in 2012 in both English and German, presents not only letters and postcards of John Lennon, but also autographs and ordinary to-do lists. It is deplorable that, for one thing, the book presents only a selection of a much larger archive of documents, and that the context of the letters is not clear to the reader. For another, there is no uniformity in the transcription and/or reproduction of Lennon's writings, and therefore it is particularly in the German versions that his plays on words are lost. That said, the reader can still get a feel for the Beatles’ founder's humour, especially through his drawings. Readers will also find interesting details about his bandmates and the creation of certain songs.